α-Secretase in Alzheimer's Disease and Beyond: Mechanistic, Regulation and Function in the Shedding of Membrane Proteins - Vincent, Bruno; Checler, Frederic (Current Alzheimer Research, 2012)
Proteases regulate numerous physiological functions in all living organisms. Because of their contribution to βAPP processing, α-, β- and γ-secretases have focused particular attention of researchers in the field of Alzheimer's disease (AD) during the past 20 years. Whereas the β-secretase BACE1 and the heterotetrameric presenilin-dependent γ- secretase complex were identified between 1995 and 2002, α-secretase activity was attributed to previously described ADAM10 and ADAM17, two members of the type I integral membrane protein family called ADAMs (A Disintegrin And Metalloprotease). ADAM10 and/or ADAM17 target numerous substrates through various modes of action. This review focuses on the complex physiology of these α-secretases and will document their contribution to cancers, diabetes, rheumatoid arthritis, and prion diseases besides their well characterized role in Alzheimer's disease.
Keywords: GPI-anchored substrates